Analisis Aplikasi Filter FIR dan Filter IIR dalam Pra-pemrosesan Sinyal Elektroensefalografi - Caroline Caroline; Nabila Husna Shabrina; Melania Regina Ao; Nadya Laurencya; Vanessa Lee (Ultima Computing : Jurnal Sistem Komputer, 2020)
Abstract – Electroencephalography (EEG) is a method used to analyze brain activities, detect abnormalities in brain, and diagnose brain-related disease. To extract information from EEG signal, preprocessing steps such as Fast Fourier Transform (FFT), filter, and wavelet decomposition will be needed. This paper primarily focuses on implementation of Finite Impulse Response (FIR) and Infinite Impulse Response (IIR) filter design in EEG signal preprocessing in MATLAB software. The result of the simulation indicates that each filter design implemented in EEG preprocessing has different performance and side effect toward signal processing parameters such as phase distortion, amplitude ratio, and processing time. Filter design type implementation also affect power and entropy calculation result. Keywords – EEG, FIR filter digital, IIR filter digital, Wavelet Decomposition, GUI-MATLAB